P152 Bowel ultrasound as an early monitoring tool to assess disease activity in Crohn's disease patients after induction therapy with infliximab. (27th May 2021) - Morão, B; Nascimento, C; Frias Gomes, C; Gonçalves, T; Castro, F; Moreira, M J; Cotter, J; Pereira, F; Caldeira, A; Sousa, R; Coelho, R; Macedo, G; et al.
Abstract: Background: Bowel wall thickness (BWT) is an accurate sonographic parameter to assess disease activity in Crohn's disease (CD). International Bowel Ultrasound Segmental Activity Score (IBUS-SAS) was developed to allow a reproducible assessment of intestinal inflammation in CD using bowel ultrasound (IUS). Aim: to assess BWT and IBUS-SAS variation after induction therapy with infliximab (IFX) and their correlation with clinical and laboratory parameters. Methods: Prospective multicentre study including patients with active CD starting IFX. Harvey-Bradshaw index (HBI), C-reactive protein (CRP), faecal calprotectin (FC) and IUS were performed at week 0 (W0) and 14 (W14). IUS response and remission were defined as a reduction in BWT ≥25% and its normalization(≤3mm) in the most affected segment, respectively. IBUS-SAS was calculated using BWT, Doppler signal, bowel wall stratification (BWS) and inflammatory fat. Results: We included 37 patients (62% males; median age 30 years, range 16–73). According to Montreal classification, most patients were A2 (70%), had ileocolonic disease (L3 57%) and an inflammatory phenotype (B1 60%); 41% had perianal disease. Most were anti-TNF therapy naive(84%), and combination therapy was used in 62%. Terminal ileum was the most affected segment identified by IUS (60%). Table 1 shows clinical, laboratory and sonographic parameters [median (IQR)]. At W14, 81% were in clinical remission, 43% in laboratorial remission (normal CRP and FC), 24% had IUS response and 11% had IUS remission. There was a significant reduction in HBI, CRP, FC and sonographic parameters (except for BWS) between W0 and W14. We found a fair to good correlation between BWT and HBI(r=0.363, p=0.03), CRP(r=0.391, p=0.02) and FC(r=0.373, p=0.03) at W14. IBUS-SAS had also a fair to good correlation with CRP(r=0.340, p=0.04) and FC(r=0.527, p=0.001) at W14. The area under the curve of IBUS-SAS for predicting clinical and laboratorial remission was 0.60; best-cut off 64.65 (sens. 57%; specif. 63%). Conclusion: There was a significant reduction in sonographic parameters after 14 weeks of IFX and one quarter of our patients had an IUS response, suggesting that reduction in BWT could be an early marker of response to therapy. We found a good correlation between IUS and clinical and laboratory parameters at W14. IUS evaluation after induction therapy can be a helpful tool to monitor disease activity and guide CD patient management in our daily practice.